2014
DOI: 10.1364/ol.39.000997
|View full text |Cite
|
Sign up to set email alerts
|

Direct amplification of a nanosecond laser diode in a high gain diode-pumped Nd:YVO_4 amplifier

Abstract: We demonstrate that Nd:YVO₄ can efficiently amplify a nanosecond laser diode in a very simple double-pass configuration. Based on longitudinal pumping with a high brightness fiber-coupled laser diode at 808 nm (60 W, 100 μm, 0.22 NA) and a low Nd-doped (0.2%) temperature controlled Nd:YVO₄ we achieved an optical gain of 62 dB with very low (<2%) parasitic laser emission and an average output power of 10 W. At 15 kHz, we observed a strong gain saturation dynamic resulting in a pulse duration reduction from 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…It can be obviously seen that the power gain achieved in the double-pass MOPA architecture is generally larger than that obtained from the single-pass MOPA architecture, especially for the low input seed power. Experimental results also manifestly reveal that the power gain decreases by increasing the input seed power for both configurations, this is a typical behavior for the power amplifier [13], [15], [16]. When the input seed power is changed from 0.8 to 50 W, the power gains are experimentally found to decrease from 8 to 2.16 for the double-pass MOPA frame and from 2.95 to 1.76 for the single-pass MOPA frame, respectively.…”
Section: Comparative Investigation Between Double-mentioning
confidence: 62%
See 1 more Smart Citation
“…It can be obviously seen that the power gain achieved in the double-pass MOPA architecture is generally larger than that obtained from the single-pass MOPA architecture, especially for the low input seed power. Experimental results also manifestly reveal that the power gain decreases by increasing the input seed power for both configurations, this is a typical behavior for the power amplifier [13], [15], [16]. When the input seed power is changed from 0.8 to 50 W, the power gains are experimentally found to decrease from 8 to 2.16 for the double-pass MOPA frame and from 2.95 to 1.76 for the single-pass MOPA frame, respectively.…”
Section: Comparative Investigation Between Double-mentioning
confidence: 62%
“…To date, most of the Nd:YVO 4 amplifiers are based on the single-pass configuration [12]- [14]. However, some recent works have shown that the double-pass architecture seems to be a more efficient design for scaling the output power of the pulsed oscillator [15], [16]. In this work, an efficient high-power MOPA based on the multi-segmented Nd:YVO 4 crystal is successfully realized for emitting output power greater than one hundred watts in the continuous-wave operation.…”
mentioning
confidence: 99%
“…The automated slide scanner setup relies on a first generation of the Pathfinder™ (Imstar S.A., France) slide scanner, composed of an epifluorescence inverted microscope (Eclipse Ti-E, Nikon, Japan) with a customized motorization (Imstar). For the fluorescence illumination in a pulse regime, we built our own laser system based on a modulated laser diode at 1064 nm wavelength amplified in a Nd 3+ :YVO4 crystal, following our previously published design [45]. We slightly modified this design to achieve sub-nanosecond (≈100 ps) pulse duration.…”
Section: Time-gated Fluorescence Microscopementioning
confidence: 99%
“…The pathway to higher pulse energies requires the use of higher saturable absorption, which inevitably leads to longer pulse durations and high intracavity power density. A different approach relying on a master oscillator and a high efficiency amplifier stage makes a master oscillator power amplifier (MOPA) configuration become more flexible and power-scalable [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%